A Lighting Mechanism for Flat Electron Emission Lamp - Li, Jung-Yu; Liu, Ming-Chung; Lin, Yi-Ping; Chen, Shih-Pu; Hsieh, Tai-Chiung; Wang, Po-Hung; Chiang, Chang-Lin; Jeng, Ming-Shan; Lee, Li-Ling; Zeng, Hui-Kai; Juang, Jenh-Yih (IntechOpen, 2012)
None